PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Sari, Lili Nur Indah (IAIN PADANGSIDIMPUAN, 2016)
Learning Instructional is a set of learning sources that are arranged for students and teachers guide in teaching learning process. Learning Instructional consists of syllabus, lesson plan, materials, studentsâ€™ worksheet, learning media, and test to measure studentsâ€™ ability. Cooperative learning is a successful teaching strategy in which small teams, each with students of different levels of ability, use a variety of learning activities to improve their understanding of a subject. Jigsaw is aÂ grouping strategy in which the members of the class are organized into jigsaw groups. The students are then reorganized into expert groups containing one member from each jigsaw group. The members of the expert group work together to learn the material or solve the problem, then return to their jigsaw groups to share their learning. By using learning instructional bases jigsaw cooperative learning type in teaching learning process, hopefully teaching learning process becomes more effective.